2022
DOI: 10.1111/jeu.12929
|View full text |Cite
|
Sign up to set email alerts
|

Sterols of Testudodinium testudo (formerly Amphidinium testudo): Production of the Δ8(14) sterol gymnodinosterol and chemotaxonomic relationship to the Kareniaceae

Abstract: Testudodinium testudo is a peridinin‐containing dinoflagellate recently renamed from Amphidinium testudo. While T. testudo has been shown via phylogenetic analysis of small subunit ribosomal RNA genes to reside in a clade separate from the genus Amphidinium, it does possess morphological features similar to Amphidinium sensu stricto. Previous studies of Amphidinium carterae and Amphidinium corpulentum have found the sterols to be enriched in Δ8(14) sterols, such as 4α‐methyl‐5α‐ergosta‐8(14),24(28)‐dien‐3β‐ol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The balance of evidence of several studies on dinoflagellate sterol compositions over the last couple of decades indicates that, in general, dinoflagellates with similar phylogenies produce similar sets of sterols, thus reinforcing the conclusions of Leblond et al (2010). In some cases this has yielded surprises, such as the dinoflagellate T. testudo , which is phylogenetically close to members of the Kareniacae (Horiguchi et al, 2012), being found to produce one of the major sterols common to these dinoflagellates (Leblond et al, 2022). This being said, dinoflagellates are evolutionarily complex organisms with unknown twists and turns in their evolution, and there will no doubt be surprises in sterol composition and/or other phenotypic traits currently considered to be consistent with phylogenetic placements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The balance of evidence of several studies on dinoflagellate sterol compositions over the last couple of decades indicates that, in general, dinoflagellates with similar phylogenies produce similar sets of sterols, thus reinforcing the conclusions of Leblond et al (2010). In some cases this has yielded surprises, such as the dinoflagellate T. testudo , which is phylogenetically close to members of the Kareniacae (Horiguchi et al, 2012), being found to produce one of the major sterols common to these dinoflagellates (Leblond et al, 2022). This being said, dinoflagellates are evolutionarily complex organisms with unknown twists and turns in their evolution, and there will no doubt be surprises in sterol composition and/or other phenotypic traits currently considered to be consistent with phylogenetic placements.…”
Section: Resultsmentioning
confidence: 99%
“…As a class, many dinoflagellates have been observed to produce dozens of sterols, including 4‐desmethyl sterols like cholesterol (cholest‐5‐en‐3β‐ol) and 4α‐methyl‐substituted sterols such as dinosterol (4α,23,24‐trimethyl‐5α‐cholest‐22E‐en‐3β‐ol; Leblond et al, 2010; Volkman, 1986, 2003; Volkman et al, 1998). As evidenced by the first review by Volkman (1986) and continuing to the present with the latest studies (Leblond et al, 2022), dinoflagellates have had their sterols characterized by many research groups over many years to elucidate their rich variety of sterols, which are arguably unparalleled in their diversity when compared to other algal groups.…”
mentioning
confidence: 99%
“…The genus Amphidinium is indeed large and diverse [see discussion in Leblond et al, 2022], and it should not be a surprise that there is no sterol(s) that amply covers the entire genus as a possible major sterol biomarker. Indeed, these results demonstrate that caution should be used when considering Δ 8(14) sterols, such 4α‐methyl‐5α‐cholest‐8(14)‐en‐3β‐ol and 4α,23,24‐trimethyl‐5α‐cholest‐8(14),22E‐dien‐3β‐ol, as Amphidinium ‐wide major sterol biomarkers because of their lesser abundance (compared with previously determined Δ 8(14) sterol distributions in A. carterae and A. corpulentum ).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in the recent study of the sterols of T. testudo by Leblond et al (2022), there have been two known exceptions to Δ 8( 14) nuclear unsaturation as a major sterol biomarker trait in sterols of Amphidinium species. Specifically, photosynthetic Amphidinium massartii Biecheler and heterotrophic Amphidinium longum Lohmann (Chu et al, 2009;Leblond et al, 2010) have been observed to produce cholesterol as a major sterol instead of the Δ 8( 14) sterols mentioned above-in fact, A. massartii was observed to cluster with cholesterol-and dinosterol-producing dinoflagellates rather than with A. carterae and A. corpulentum (Leblond et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation